Associação entre a presença de HIV e síndromes geriátricas em pessoas de meia idade: um estudo caso-controle - Titon, Joana Perotta (2020)
Introduction: The human immunodeficiency virus (HIV) infection causes depletion of CD4 + T lymphocytes, as well as a telomere shortening of these cells and increase in inflammatory mediators. All these characteristics are also observed in aging. Chronically infected patients have symptoms that resemble geriatric syndromes (GS). There is a higher prevalence of GS in older people and there seems to be a tendency for early appearing of them in HIV patients. However, reviewing literature, we did not identify studies that evaluate more than one GS using the Comprehensive Geriatric Assessment (CGA), comparing people with and without HIV. The objective of this research was to assess the association between the presence of GS and exposure to HIV. Method: Case-control study conducted in 2019 in adults aged 50 years-old or more in a specialized HIV care service and in basic health units in Francisco Beltrão, Brazil. 52 HIV cases and 104 non-HIV controls matched for age, sex and neighborhood were evaluated. A sociodemographic questionnaire and validated CGA tests were applied. The Chisquare test with Yates continuity correction and the Mann-Whitney U test were used for statistical analysis. Results: The mean age of the sample (n=156) was 60 ± 7.8, with 61.5% being female. Cases used fewer medications (p=0.019), have lower abdominal circumference (p=<0.001), arm circumference (p=0.001), calf circumference (p<0.001), body mass index (BMI) (p=0.001) and muscle mass index (IMM) (p<0.001), and higher walking speed (p=0.017). When analyzing GS, a higher proportion of normal weight and low weight was identified in cases compared to controls (p=0.001). Of the total number of individuals evaluated (n=156), 41% (n=64) presented at least two GS, being 38.5% (n=20) of cases and 42.3% (n=44) of controls. Conclusion: GS occur in HIV population in the same proportion as the general population. Although Brazil is a developing country, public policies may be contributing to the achievement of good control of HIV. Thus, HIV associated with ARV does not seem to anticipate GS and these patients are in good health.